Prevalence of Metabolic Syndrome among Patients with Acute Myocardial Infarction at Al-Ramadi Teaching Hospital, Ramadi City, Iraq - Amer Hussein (Al-Anbar Medical Journal)
Background: Acute myocardial infarction (AMI) and metabolic syndrome (MeS) are two major health problems worldwide. In recent years, MeS has been introduced as a significant risk factor for AMI.Objective: To estimate the prevalence of MeS and its components among patients with AMI.Materials and Methods: This was a cross-sectional study conducted at Al-Ramadi Teaching Hospital during a period from January to December 2022, including a total of 100 patients with AMI. The definition of MeS was established based on the criteria of the modified National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III).Results: The mean age of patients was 58.6 ± 7.1 (range: 41–81 years). Males represented 55% of the studied group. Clustering of MeS components among cases revealed that 57% had less than three components while 43% had 3 or more criteria for MeS diagnosis, giving a prevalence rate of 43% for MeS. Only 5 cases had none of these components. MeS was relatively more prevalent in younger age groups and females. The mean values of all components of MeS were significantly higher in the MeS group than in the non-MeS group (P-value < 0.05).Conclusion: MeS was an important risk factor for AMI. The study revealed a high prevalence of MeS among individuals with AMI and it was higher among women than men.